Investigating the Relationship Between Worker Demographics and Nature of Injury on Federal Department of Defense Workers' Compensation Injury Rates and Costs From 2000 to 2008. (March 2015) - Mallon, Timothy M.; Cherry, Scott E.
Abstract : Objective: This is the first study of workers' compensation injuries and costs in Department of Defense workers that examined whether any demographic factors including age, sex, occupation, and nature of injury altered the risks or costs of an injury or illness over time. Methods: Department of Defense Workers' Compensation claims for period 2000 to 2008 were analyzed ( n = 142, 115) using Defense Portal Analysis and Defense Manpower Data Center to calculate injury rates and costs. Regression analysis was done using SPSS to examine the change in the risk of injury or illness over time from 2000 to 2008. Results: The age group of 30 to 34 years had the lowest costs per claim and highest claims rate, 332 per 10, 000. The age group of 65 to 70 years had the lowest claims rate of 188 per 10, 000 but the highest costs per claim. Claims cost increased $69 for each 5-year group, and older workers had a threefold increase in costs per claim. Conclusion: Younger workers get hurt more often, but older workers tend to have more expensive claims.